2008
DOI: 10.1111/j.1365-3148.2008.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

How much residual plasma may cause TRALI?

Abstract: Although passive infusion of plasma-rich components containing white blood cell (WBC) antibodies are responsible for majority of the reported transfusion-related acute lung injury (TRALI) cases, the minimum volume of residual plasma, which might trigger TRALI, is not known. We report three cases of TRALI where the implicated donor component contained between 10 and 20 mL of residual plasma. Two cases were related to transfusion of red blood cells prepared in optimal additive solution, and the other was related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 18 publications
(20 reference statements)
1
62
0
1
Order By: Relevance
“…Furthermore, plasma volumes in RBCs units as small as 10 to 20 mL containing donor-derived antibodies are sufficient to cause TRALI. 50 Our results suggest that either exclusion of all female donor blood for preparation of all blood products or exclusion of those tested positive for the presence of antibodies may reduce TRALI incidence. A policy of screening and excluding donors based on a certain cut-off titer of HLA/HNA antibodies 51 may not reduce TRALI incidence in patients with a priming condition, as experimental data suggest that the presence of a "first event" requires a lower titer of HLA/HNA antibodies for the onset of TRALI.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, plasma volumes in RBCs units as small as 10 to 20 mL containing donor-derived antibodies are sufficient to cause TRALI. 50 Our results suggest that either exclusion of all female donor blood for preparation of all blood products or exclusion of those tested positive for the presence of antibodies may reduce TRALI incidence. A policy of screening and excluding donors based on a certain cut-off titer of HLA/HNA antibodies 51 may not reduce TRALI incidence in patients with a priming condition, as experimental data suggest that the presence of a "first event" requires a lower titer of HLA/HNA antibodies for the onset of TRALI.…”
Section: Discussionmentioning
confidence: 80%
“…Transfusion of plasma is associated with transfusion-related acute lung injury (TRALI) [6], the leading cause of transfusion-related deaths in North America. It has been suggested that larger volumes of residual plasma in RCCs could be associated with an increased risk of TRALI [1,7]. In addition to clinical outcomes, there is also interest in how residual plasma influences in vitro RCC quality during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRALI is most often caused by the FFP, 9 but has also been described after RBC transfusions. 10 -12 Win et al 13 showed that residual plasma volume, as little as 10 to 20 ml, may induce TRALI. In our study, the imputative RBC concentrate contained about 10 ml of residual plasma, with very high levels of HLA antibodies, specific to graft antigens.…”
Section: Discussionmentioning
confidence: 98%